2005
DOI: 10.1021/es049025e
|View full text |Cite
|
Sign up to set email alerts
|

Dual Electrodes Oxidation of Dye Wastewater with Gas Diffusion Cathode

Abstract: The high energy cost of an electrochemical method is the fatal drawback that hinders its large scale application in wastewater treatment. In traditional single-chamber electrolysis cell, only direct oxidation at an anode exists. Although a small amount of hydrogen peroxide is produced at the cathode by reduction, it is transferred to the anode and destroyed there without adding much benefit to organic decomposition. A two-chamber electrolytic cell, connected with an electrolyte bridge, was developed in this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…The electrochemical oxidation process will not be economical because of the high-energy consumption that hinders its large scale application. Since the 1990s, there has been an increasing interest in the indirect oxidation of organic pollutions by reactive species such as hydrogen peroxide, which are generated on the cathode which cut the energy cost dramatically (Shen et al, 2005;Brillas et al, 1995). Although the degradation efficiency of the reactive species has been largely researched and several possible mechanisms of indirect electrochemical oxidation have brought forward, to the authors' knowledge, few of them have adequate and instantaneous evidence about the generation mechanism of the reactive species, especially radicals on the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical oxidation process will not be economical because of the high-energy consumption that hinders its large scale application. Since the 1990s, there has been an increasing interest in the indirect oxidation of organic pollutions by reactive species such as hydrogen peroxide, which are generated on the cathode which cut the energy cost dramatically (Shen et al, 2005;Brillas et al, 1995). Although the degradation efficiency of the reactive species has been largely researched and several possible mechanisms of indirect electrochemical oxidation have brought forward, to the authors' knowledge, few of them have adequate and instantaneous evidence about the generation mechanism of the reactive species, especially radicals on the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the individual and interactive impacts of treatment parameters on reaction were concentrated on 3D response surface graph from created numerical models. Optimization of treatment factors for the most effective treatment productivity was completed by Derringer's desired function strategy utilizing numerical optimizing technique 17 .…”
Section: Methodsmentioning
confidence: 99%
“…A review of the previous work have been undertaken in order to achieve a systematic and proper procedure for accomplishing the aim of this investigation. During the review of the published material it was found that great emphasis had been put on treating various industrial effluents using electrochemical methods [5][6][7][8] . The electrochemical processes involve the direct reaction of species at electrode surface, while others involves the production of active species at the electrode and further reaction with the targeted pollutants.…”
Section: Introductionmentioning
confidence: 99%